CDE Emotional Dependence Questionnaire: Evidence of Validity and Reliability in Colombian samples - Prieto Patiño, Luis Enrique (2025)
Objective. The purpose of this research was to study the psychometric properties of the Lemos and Londoño Emotional Dependence Questionnaire (2006). Method. A total of 634 participants, aged between 18 and 50 years, completed the instrument. Results. A five-factor structure was found, which was confirmed by confirmatory factor analysis: separation anxiety (6 items, ω = 0.892), partner´s affective expression (4 items, ω = 0.854), fear of loneliness (3 items, ω = 0.870), modification of plans (3 items, ω = 0.814), and borderline expression (3 items, ω = 0.853). This structure contrasts with the six factors proposed in the original scale. The adequate psychometric results suggest that this is a valid and reliable instrument for measuring emotional dependence.